Resource use efficiency among rice farmers around fragile ecosystems: evidence from Kilombero Wetland, Tanzania - Kamau, Philip; Willy, Daniel; Ngare, Lucy (Applied Studies in Agribusiness and Commerce, 2020)
Farmers have been encroaching fragile wetlands as a strategy to increase their rice production thus threatening wetlands’ existence and capacity to other critical ecosystem services. This calls for efficient production to strike the balance between food rice production and wetlands’ sustainable existence. The current study sought to provide assess rice farmers’ technical efficiency of resource use by detecting the determinants of rice yield and further identify the determinants of technical efficiency of the resources used by rice farmers in Kilombero wetland. A cross-sectional survey of 145 randomly sampled farmers aided in achieving the study objective. A stochastic frontier analysis (SFA) model was used to analyze data. The mean technical efficiency among farmers was at 60.54% level. The positive determinants of rice yield were land and fertilizers while labor influenced it negatively. Age, education, farming experience, group membership, and credit access reduced inefficiency while the distance to the extension agent and off-farm income increased farmers’ inefficiency. The study concludes that there is a possibility of expanding rice production without threatening the wetland’s existence. It recommends that government and other stakeholders to ensure that rice farmers are up-to-date with optimal use of fertilizers in rice production since it will assist in improving rice yield while the rate of expansion of rice lands in the wetlands will lower. Policy implementers ought to establish initiatives that inspire rice farmers to capitalize on farmer groups and join education programs to take full advantage of their potential efficiency and might participate in community development activities. JEL code: Q15